Current progress and future perspectives of neoadjuvant anti-PD-1/PD-L1 therapy for colorectal cancer - Yang, Zhengyang; Wu, Guocong; Zhang, Xiao; Gao, Jiale; Meng, Cong; Liu, Yishan; Wei, Qi; Sun, Liting; Wei, Pengyu; Bai, Zhigang; Yao, Hongwei; Zhang, Zhongtao (Frontiers in Immunology, 2022)
Immunotherapies, especially the programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) inhibitors have revolutionized the therapeutic strategies of various cancers. As for colorectal cancer, the current clinical application of PD-1/PD-L1 inhibitors are mainly used according to the mutation pattern, which is categorized into deficient mismatch repair (dMMR) / high levels of microsatellite instability (MSI-H) and proficient mismatch repair (pMMR) or non-high levels of microsatellite instability (non-MSI-H). PD-1/PD-L1 inhibitors have been proved with favorable outcomes against dMMR/MSI-H colorectal cancer because of more T cell infiltration into tumor tissues. Nevertheless, the effectiveness of PD-1/PD-L1 inhibitors in pMMR/non-MSI-H colorectal cancer is still uncertain. Because of the quite lower proportion of dMMR/MSI-H in colorectal cancer, PD-1/PD-L1 inhibitors have been reported to combine with other antitumor treatments including chemotherapy, radiotherapy and targeted therapy for better therapeutic effect in recent clinical trials. Neoadjuvant therapy, mainly including chemotherapy and radiotherapy, can not only reduce clinical stage, but also benefit from local control, which can improve the clinical symptoms and improve quality of life. Adding immunotherapy into neoadjuvant therapy may change the treatment strategy of primary resectable or some metastatic colorectal cancer. In this review, we focus on the development of neoadjuvant anti-PD-1/PD-L1 therapy and discuss the future perspectives in colorectal cancer.